Evolution of Islamic Legal Thought: From the Prophetic Era to Reform Movements - Redi Zulpianto; Rifana Wahdi; Ahmad Lidra; Julhadi Julhadi (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2026)
This study aims to analyze the development of Islamic legal thought from the time of the Prophet Muhammad (saw) to the era of modern renewal. The research uses a qualitative approach with the library research method through the analysis of primary and secondary sources related to the history and dynamics of Islamic legal thought. The data collection technique is carried out through documentation, while the data analysis uses a descriptive-analytical method. The results of the study show that Islamic legal thought develops dynamically through the interaction between the text of revelation, rationality, and the socio-historical context of society. These developments can be seen in every phase of history, starting from the normative prophetic period, the time of the Companions who emphasized ijtihad, the phase of systematic codification of the fiqh school, to the modern reform movement that seeks to reconstruct Islamic law to be relevant to the development of the times. This study concludes that Islamic law has a flexible and adaptive character so that it is able to respond to social changes without abandoning the basic principles of sharia. The findings of this research are expected to enrich the study of Islamic philosophy and legal thought and become the foundation for the development of contextual ijtihad in the modern era.